EVALUASI KEBIJAKAN PERLINDUNGAN PEREMPUAN DARI TINDAK KEKERASAN DI KOTA SEMARANG - Amalia Wijayanti; Dewi Rostyaningsih; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
Violence against women in Semarang City is an endless phenomenon because in Semarang City itself cases of violence against women are always increasing. One of the efforts made by the Semarang City government in providing protection for women from acts of violence is by ratifying Regional Regulation No. 05/2016. The purpose of this research is to evaluate how the policy is being held and describe supporting and inhibiting factors the implementation of the policy.This research uses a qualitative descriptive approach.The informant determination techniques used are purposive sampling techniques and supported using snowball sampling with data collection methods through interviews, observation and documentation.The result of this research shows that the implementation of women’s protection policy from violent acts in semarang city is considered to be good, such as the availability of facilities and infrastructure and the existence of Standard Operating Procedures as a guide for services to victims. However, there are still obstacles in its implementation such as a lack of human and financial resources, lack of commitment from agencies who are a part of integrated service center, negative stigma from society and the absence of a forum for victims to be able to provide criticisms and suggestions for the services provided.Therefore, the recommendation that can be given to the government is: carry out a sound budget allocation planning, destroying egos between agencies, needs to establish special safe place for women victims of violence and encouraging the government to urgently discuss and pass the Draft Law on the Elimination of Sexual Violence (RUU PKS) into a law.